دراسة تأثير مصفوفة القياس على أداء التحسس المضغوط للصور المدمجة في شبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة - مثنى القبيلي; غادي محمودي; دعاء محمود (Tishreen University, 2019)
Wireless Multimedia Sensor Networks (WMSNs) have been widely used in many practical applications. Data reduction techniques such as image fusion and compression are useful in eliminating data redundancy and reducing transmission power. Compression using the Compressive Sensing (CS) technique is characterized by low complexity of its implementation in the sensor nodes, and this fits the limited resources of these nodes. In this research, we study the case of fusing two images taken from two sensor nodes with overlapping field of view. The fused image is compressed using compressive sensing on the base of three different types of measurement matrices: Gaussian matrix, Toeplitz matrix and Scrambled Block Hadamard Ensemble (SBHE).  The performance of these matrices is compared in relation to different parameters that evaluate the quality of the reconstructed image and the power consumption at different numbers of measurements. The results show that the adoption of SBHE ensures lower energy consumption compared with the adoption of Gaussian matrix or Toeplitz matrix at different compression ratios. Nevertheless, SBHE allowed the best quality of the reconstructed image compared to the other two matrices. تُستخدم شبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة بشكلٍ واسع في العديد من التطبيقات العملية. تفيد تقنيات تخفيض المعطيات كدمج الصور والضغط في إزالة الفائض من البيانات المكررة وتخفيض طاقة الإرسال في هذه الشبكات. يتميز الضغط باستخدام تقنية التحسس المضغوط بانخفاض تعقيد تنفيذه في العقد الحساسة، وهذا ما يلائم محدودية الموارد في هذه العقد. تمّت الاستفادة، في هذا البحث،  من دمج صورتين ملتقطتين من عقدتين حساستين تملكان حقلي رؤية متراكبين. تمّ ضغط الصورة الناتجة عن الدمج  باستخدام التحسس المضغوط اعتماداً على ثلاثة أنواع مختلفة من مصفوفات القياس وهي: المصفوفة الغوصية، ومصفوفة تويبلتز ومصفوفة هادامارد الكتلية الممزوجة SBHE . قورن أداء هذه المصفوفات اعتماداً على بارامترات مختلفة تقيّم جودة الصورة المستعادة واستهلاك الطاقة وذلك عند عددٍ مختلف من القياسات. تظهر النتائج أنّ اعتماد مصفوفة هادامارد الكتلية الممزوجة يضمن استهلاك طاقة أقل مقارنةً مع اعتماد المصفوفة الغوصية أو مصفوفة تويبلتز وذلك عند مختلف نسب الضغط. رغم ذلك أتاحت مصفوفة هادامارد الكتلية الممزوجة أفضل جودة للصورة المستعادة مقارنةً مع المصفوفتين الأخرتين.